Pernikahan Dini di Indonesia: Ancaman bagi Kesehatan Reproduksi dan Masa Depan Wanita - Astuti, Elly Novie (Maliki Interdisciplinary Journal, 2025)
Early marriage is a significant social phenomenon in Indonesia, especially among communities with low economic levels and deeply rooted cultures. This research aims to examine the impact of early marriage on women's reproductive health and their future. Research results show that early marriage is often caused by traditional factors, family economic conditions, and unwanted pregnancies (KTD). Reproductive health impacts include the risk of pregnancy complications, anemia, miscarriage and postpartum hemorrhage, which can threaten the lives of the mother and baby. In addition, women who marry early tend to experience dropping out of school, limited access to decent work, and decreased participation in social and economic development. This phenomenon also has a negative impact on society at large, especially in exacerbating gender gaps and slowing development progress. Therefore, efforts to prevent early marriage through education, economic empowerment and cultural transformation are very necessary to protect women's rights and support inclusive development.